Investigation on Optical and Biological Properties of 2‐(4‐Dimethylaminophenyl)benzothiazole Based Cycloplatinated Complexes. Issue 63 (7th October 2021) - Lara, Rebeca; Millán, Gonzalo; Moreno, M. Teresa; Lalinde, Elena; Alfaro‐Arnedo, Elvira; López, Icíar P.; Larráyoz, Ignacio M.; Pichel, José G.
Abstract: The optical and biological properties of 2‐(4‐dimethylaminophenyl)benzothiazole cycloplatinated complexes featuring bioactive ligands ([Pt(Me2 N‐pbt)(C6 F5 )L] [L=Me2 N‐pbtH 1, p ‐dpbH (4‐(diphenylphosphino)benzoic acid) 2, o ‐dpbH (2‐(diphenylphosphino)benzoic acid) 3 ), [Pt(Me2 N‐pbt)( o ‐dpb)] 4, [Pt(Me2 N‐pbt)(C6 F5 )2 (μ‐PR n P)] [PR4 P=O(CH2 CH2 OC(O)C6 H4 PPh2 )2 5, PR12 P=O(CH2 CH2 O)3 C(O)C6 H4 PPh2 2 6 ] are presented. Complexes 1 –6 display 1 ILCT and metal‐perturbed 3 ILCT dual emissions. The ratio between both bands is excitation dependent, accomplishing warm‐white emissions for 2, 5 and 6 . The phosphorescent emission is lost in aerated solutions owing to photoinduced electron transfer to 3 O2 and the formation of 1 O2, as confirmed in complexes 2 and 4 . They also exhibit photoinduced phosphorescence enhancement in non‐degassed DMSO due to local oxidation of DMSO by sensitized 1 O2, which causes a local degassing. Me2 N‐pbtH and the complexes specifically accumulate in the Golgi apparatus, although only 2, 3 and 6 were active against A549 and HeLa cancer cell lines, 6 being highly selective in respect to nontumoral cells. The potential photodynamic property of these complexes was demonstrated with complex 4 . Abstract : Biocompatible photosensitizers : Mono‐ and dinuclear cycloplatinated complexes featuring the donor–acceptor 2‐(4‐dimethylaminophenyl)benzothiazolyl ligand (Me2 N‐pbt) and biologically active phosphines show dual emission and photoinduced phosphorescence generating 1 O2, with potential applications in theranostics and photodynamic therapy.